H.M. Bateman : the man who went mad on paper - Bateman, Henry M. (The Cartoon Museum, 2012)
Every line speaks for itself : the life of H.M. Bateman /Anita O'Brien --The early drawings /John Jensen --Logical impossibilities : the strip cartoons of H.M. Bateman /Anthony Anderson --The pictures --A perfectly serious business : H.M. Bateman's humorous drawing /Anita O'Brien.